2021
DOI: 10.3389/fcell.2021.647197
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Relationship Between Alzheimer’s Disease and Cancer With a circRNA Perspective

Abstract: BackgroundIncreasing evidence indicates an association between the incidence of Alzheimer’s disease (AD) and cancer development. Despite advances being made by comparisons from epidemiological studies, common pathways and molecular mechanisms, little is known about the identities of the circular RNAs (circRNAs) involved in the development and progression of these two pathologies and their possible correlations. The aim of this study was to explore the circRNA relationship between AD and cancer.Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Previous studies have assessed the usefulness of several of our discovered candidate pharmacological agents targeting affected AD pathways. Converging evidence indicates that cancer treatment may be related to a decreased risk of AD due to a pathophysiological overlap between both diseases, albeit a worsened cognition being in some studies linked to oncology drugs (D. Chen et al, 2021; Frain et al, 2017; Plun-Favreau et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed the usefulness of several of our discovered candidate pharmacological agents targeting affected AD pathways. Converging evidence indicates that cancer treatment may be related to a decreased risk of AD due to a pathophysiological overlap between both diseases, albeit a worsened cognition being in some studies linked to oncology drugs (D. Chen et al, 2021; Frain et al, 2017; Plun-Favreau et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we recently found that the expression pattern of circRNA inversely correlated between some cancers and Alzheimer’s disease, suggesting that they may share some common circRNA-mediated mechanisms and pathogenesis. 48 Such analysis would require further fine-tuning of the mining algorithms and obtaining additional mRNA/circRNA expression profiles under specific conditions. Another potential technical extension of CRIT is to apply supervised-learning algorithms to predict circRNA-regulating RBPs based on known or validated regulators.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly useful in personal drug prescriptions in cancer care and/or combating drug resistance. In addition, accumulated evidence revealed that some cancers share common mechanisms and molecular pathogenesis with neurodegenerative diseases, such as Alzheimer's disease (AD) [64,65]. Thus, this framework can be utilized as a computational tool for generating mechanistic hypotheses and drug replacement for both cancer and AD when the drug activity and multi-omics data are comprehensive.…”
Section: Discussionmentioning
confidence: 99%